PERANAN GURU PENDIDIKAN AGAMA ISLAM DALAM MEMBINA AKHLAK PESERTA DIDIK - Nur Azizah; M. Nasor; Nina Ayu Puspita Sari (UNISAN JURNAL, 2024)
This examination plans to break down and describe the capabilities completed by PAI educators in aiding understudies at Mathla'un Nur Professional School, Metro City, work on their ethics. This is finished to make sense of this job. Since the approach depends on subjective proof, this examination is subjective in nature. In this examination, documentation studies, meetings and perceptions are the techniques used to gather information. In the mean time, there are three phases in information examination: diminishing information, showing information, and making ends. The discoveries of exploration directed on 180 understudies at Mathla'un Nur Professional School in Metro City showed that a normal of 16% of understudies had low ethics. Interestingly, 84% of understudies have high ethics, which incorporate profound quality towards friends, educators and staff, as well as moral obligation regarding errands and following school arrangements. This shows that most of understudies have great ethics. Because of the low number of gatherings between PAI educators and understudies, absence of endeavors to screen understudy progress through portfolio evaluations, less serious endeavors to impart virtues in understudies, and absence of authority of the material, the job of PAI educators as teachers and teachers isn't ideal.